More Flavor for Flavonoid-Based Interventions?. Issue 4 (April 2017) - Kaakoush, Nadeem O.; Morris, Margaret J.
Abstract : Poor diets are associated with obesity and a decline in cognitive function. Flavonoids are plant compounds that have been associated with improved metabolic parameters in obesity and reversal of cognitive decline. Given that microbial flavonoid conversion is important for bioactivity, flavonoid-derived neuroactive compounds may be functionally crucial in the gut microbiome–brain axis.